Anti-pulverization molded wood activated carbon and preparation method thereof
Patent Information
- Application Number
- CN202611443982.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-17
- Publication Date
- 2026-11-03
AI Technical Summary
Existing molded activated carbon is prone to pulverization during use, resulting in decreased adsorption efficiency and insufficient mechanical stability. It is particularly difficult to meet the requirements for cleanliness and mechanical stability in applications such as automotive exhaust treatment systems and air purifier filters.
After hydroxylating the wood charcoal powder, it is modified with a silane coupling agent containing thiol to form thiolized wood charcoal powder. Then, it undergoes a click reaction with an alkenyl aromatic aldehyde under ultraviolet light to form a stable thioether bond. Finally, it undergoes covalent chemical bridging with phenolic resin to improve the interfacial bonding strength between the charcoal powder and the resin.
It significantly improves the anti-pulverization performance of molded wood-based activated carbon, reduces the pulverization abrasion coefficient, and increases wear resistance, making it suitable for high-cleanliness environments and scenarios involving mechanical vibration and airflow impact.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention belongs to the field of activated carbon technology, specifically relating to a molded wood-based activated carbon resistant to pulverization and its preparation method. Background Technology
[0002] Activated carbon, due to its well-developed pore structure and excellent adsorption performance, is widely used in gas-phase adsorption, liquid-phase purification, catalyst support, and electrochemical energy storage. While powdered activated carbon has a high specific surface area, its low bulk density makes transportation and recycling difficult, and it easily generates dust pollution during use, making it difficult to meet the mechanical strength and cleanliness requirements of continuous industrial plants. Therefore, bonding activated carbon powder into shaped activated carbon has become the mainstream solution that balances adsorption performance and mechanical strength.
[0003] The preparation of molded activated carbon typically requires the use of binders to bond carbon powder into a shape, followed by carbonization and activation to obtain the final product. Coal tar-based binders offer high molding strength but pose environmental and safety concerns. Phenolic resins, as binders, have high residual char and good thermal stability; however, the relationship between conventional phenolic resin and carbon powder is merely a physical coating, with limited interfacial bonding strength, making them prone to pulverization under conditions such as vibration and airflow impact. Compared to coal-based activated carbon, wood-based activated carbon exhibits more severe pulverization, which is related to its highly porous structure and inherently lower mechanical strength. Pulverization of molded activated carbon not only reduces its adsorption efficiency and system cleanliness but also exacerbates wear on metering pumps and valves, making it difficult to meet the high cleanliness and mechanical stability requirements of applications such as automotive exhaust treatment systems and air purifier filters.
[0004] To address the pulverization problem of molded activated carbon, existing technologies mainly employ methods such as increasing the amount of binder and raising the molding pressure. However, increasing the amount of binder can clog the pores of activated carbon, leading to a decrease in adsorption capacity; increasing the molding pressure may destroy the original pore structure of the carbon powder particles. In addition to the above methods, researchers have also attempted to improve the anti-pulverization performance by focusing on the binder system. CN119461369A discloses a shaped activated carbon, its preparation method, and its uses. The shaped activated carbon includes activated carbon powder, cellulose binder, emulsion binder, reinforcing agent, lubricant, and solvent. Columnar or honeycomb activated carbon is obtained through kneading, slurry preparation, and extrusion molding, and can be used in automotive charcoal canisters. This method utilizes an acrylic emulsion to form a thin film layer on the surface of the molded carbon during the drying process, thereby reducing powder shedding. However, this method relies on the coating effect of the surface physical film; once the film wears or ages during use, the interfacial bonding strength decreases, and the pulverization problem recurs.
[0005] Existing technologies for improving the resistance of molded activated carbon to powdering mainly focus on surface coating, and have not yet addressed the technical approach of constructing a covalent bond interface between carbon powder and resin. Summary of the Invention
[0006] Given that the existing technology of molded wood-based activated carbon has insufficient anti-pulverization performance and that existing improvement methods are mostly limited to surface coating and fail to solve the problem of carbon powder-resin interface bonding, the present invention provides a method for preparing anti-pulverization molded wood-based activated carbon to achieve covalent chemical bridging between wood-based carbon powder and resin network, thereby improving the anti-pulverization performance of molded wood-based activated carbon.
[0007] To achieve the above objectives, the present invention adopts the following technical solution:
[0008] A method for preparing pulverized molded wood-based activated carbon includes the following steps:
[0009] S1. After hydroxylation treatment, wood charcoal powder is modified with a silane coupling agent containing thiol groups to obtain thiolized wood charcoal powder.
[0010] S2. Thiolized wood charcoal powder is dispersed in a polar aprotic solvent, and an alkenyl aromatic aldehyde and a photoinitiator are added to form a dispersion. The mass ratio of the thiolized wood charcoal powder to the alkenyl aromatic aldehyde is 100:10~20. Then, under the protection of an inert gas, the dispersion is irradiated with ultraviolet light to cause the thiol and alkenyl groups to undergo a click reaction. After the irradiation is completed, the mixture is purified to obtain modified wood charcoal powder.
[0011] S3. The modified wood charcoal powder is mixed and kneaded with thermoplastic phenolic resin, curing agent and solvent to form a mixed wet material, which is then extruded under high pressure to obtain a molded wet material; after drying, the molded wet material is heated and cured to obtain a molded wood charcoal precursor.
[0012] S4. After carbonization and activation, the shaped wood charcoal precursor is used to obtain shaped wood activated carbon resistant to pulverization.
[0013] Further, in step S1, the wood charcoal powder is selected from at least one of bamboo charcoal powder, wood charcoal powder, coconut shell charcoal powder, and walnut shell charcoal powder, and the average particle size of the wood charcoal powder is 150-400 mesh, and the specific surface area is 1800-2200 m². 2 / g, with an average pore size of 2~10 nm. The hydroxylation treatment conditions are as follows: lignocharcoal powder is soaked in a 3~6 mol / L inorganic alkali aqueous solution, subjected to hydrothermal reaction at 70~80℃ for 6~10 h, then centrifuged, washed with pure water until the filtrate is neutral, and dried at 60~80℃ to constant weight. The inorganic alkali is selected from NaOH and / or KOH.
[0014] Further, in step S1, the thiol-containing silane coupling agent is selected from at least one of 3-mercaptopropyltriethoxysilane and 3-mercaptopropyltrimethoxysilane; the modification conditions are as follows: hydroxylated wood charcoal powder, the thiol-containing silane coupling agent, and the acidic catalyst are added to an alcohol at a mass ratio of 100:(15~25):(1~3), and reacted at 60~80℃ for 3~6 hours. After the reaction is completed, the mixture is centrifuged, and the solid is washed 2~4 times with alcohol and dried at 60~80℃ to constant weight. Even further, the alcohol is selected from at least one of ethanol, propanol, and isopropanol, and the acidic catalyst is selected from at least one of p-toluenesulfonic acid and methanesulfonic acid.
[0015] Preferably, in step S2, the mass ratio of the thiolized charcoal powder to the alkenyl aromatic aldehyde is 100:10~15; and the mass of the photoinitiator accounts for 0.3~0.8 wt% of the thiolized charcoal powder.
[0016] Further, in step S2, the alkenyl aromatic aldehyde is an aromatic compound containing an alkenyl and an aldehyde group in its molecule, specifically selected from at least one of 3-(allyloxy)benzaldehyde, 4-(allyloxy)benzaldehyde, and 4-allylbenzaldehyde, preferably 3-(allyloxy)benzaldehyde or 4-(allyloxy)benzaldehyde.
[0017] Further, in step S2, the polar aprotic solvent is selected from at least one of N,N-dimethylacetamide (DMAC), N,N-dimethylformamide (DMF), and N-methylpyrrolidone (NMP); the photoinitiator is selected from at least one of 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylphenylacetone, 1-hydroxy-cyclohexyl-phenyl ketone, and 2-hydroxy-2-methyl-1-phenyl-1-propanone; the inert gas is selected from nitrogen and / or argon; the ultraviolet irradiation conditions are: the ultraviolet lamp is 5-10 cm above the surface of the dispersion, irradiated at 600-900 W for 5-10 min, and the ultraviolet lamp wavelength is 300-400 nm; the purification process is: centrifugation is performed sequentially, the solid part is washed 2-4 times with a polar aprotic solvent, and dried at 60-80℃ for 8-24 h.
[0018] During the ultraviolet irradiation process in step S2, the thiol groups on the surface of the thiolized charcoal powder undergo a click chemical reaction with the alkenyl groups in the alkenyl aromatic aldehyde, forming stable thioether bonds (CSCs), thereby stably anchoring the alkenyl aromatic aldehyde to the surface of the charcoal powder. This reaction exhibits high chemoselectivity, occurring only between the thiol and alkenyl groups, without interfering with the aldehyde groups or other functional groups. The aldehyde groups that do not participate in the reaction participate in phenolic crosslinking during the heating and curing stage in step S3. On the other hand, the alkenyl aromatic aldehyde contains an aromatic ring structure, which has relatively high thermal stability. Therefore, during the subsequent pyrolysis process, its aromatic ring structure helps the phenolic resin form a more stable carbonized structure.
[0019] Further, in step S3, the ratio of the modified wood charcoal powder to the thermoplastic phenolic resin and curing agent is 100:(20~30):(5~8), preferably 100:(25~30):(6~8). The number average molecular weight of the thermoplastic phenolic resin is 500~900; the curing agent is selected from at least one of hexamethylenetetramine, trimethylhexamethylenediamine, and diethylaminopropylamine; the solvent is an alcohol solvent, or an alcohol-water mixture with an alcohol volume percentage of 70~80%, wherein the alcohol is at least one of ethanol, propanol, and isopropanol.
[0020] Further, in step S3, the mixing and kneading temperature is 35~50℃, and the kneading and mixing time is 1~2 h; the solvent content in the mixed wet material is 10~15wt%; the high-pressure extrusion pressure is 12~18 MPa. The shape of the molded wet material is not limited and can be columnar, spherical, or honeycomb.
[0021] Furthermore, in step S3, the drying conditions are as follows: first, dry at 50~60℃ for 6~12 h, then dry at 70~90℃ for 6~12 h. This step-by-step temperature increase drying can avoid rapid water loss leading to cracking. The temperature curing conditions are as follows: heat to 150~180℃ and hold for 1~2 h to allow the phenolic resin to complete cross-linking.
[0022] During the heating and curing process in step S3, the alkenyl aromatic aldehydes anchored on the surface of the wood charcoal powder in step S2, with their aldehyde groups acting as additional crosslinking sites, participate in the crosslinking reaction of the thermoplastic phenolic resin together with the curing agent, forming a covalent bond between the wood charcoal powder and the resin network, rather than a simple physical coating. This significantly improves the interfacial bonding strength of the molded wood activated carbon, thereby improving its anti-pulverization performance.
[0023] Further, in step S4, the carbonization conditions are as follows: under an inert atmosphere, the temperature is increased to 500-700℃ at a heating rate of 5-10℃ / min, and held for 1-3 hours. The activation conditions are as follows: at 850-1050℃, water vapor is introduced, and activation is carried out for 2-4 hours.
[0024] Secondly, the present invention provides pulverized molded wood-based activated carbon prepared by the above-described preparation method.
[0025] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0026] 1. This invention utilizes the high selectivity of the mercapto-alkene click reaction to anchor alkenyl aromatic aldehydes onto the surface of wood charcoal powder. During the subsequent phenolic resin bonding and molding process, the aldehyde groups of the aromatic aldehydes act as second crosslinking sites in the phenolic crosslinking network, thereby achieving a covalent chemical bridge between the wood charcoal powder and the resin binder. This approach differs from conventional physical binder systems by introducing chemical bonds at the charcoal powder-resin interface, significantly improving the interfacial bonding strength of the molded wood activated carbon and thus enhancing its anti-pulverization properties.
[0027] 2. The molded wood-based activated carbon prepared by the method of this invention has a pulverization abrasion coefficient (ASTM D5159 standard) ≤0.35 mg / g·min and a wear resistance (GB / T 12496.6) ≥93%, making it suitable for scenarios with high cleanliness requirements or those that need to withstand strong mechanical vibration and airflow impact, such as automotive fuel evaporation emission treatment systems and air purifier filters. Detailed Implementation
[0028] The present invention will be further described below with reference to specific embodiments, but the present invention is not limited to the following embodiments.
[0029] Unless otherwise specified, the experimental methods described in the following examples are conventional methods; unless otherwise specified, the reagents and materials are commercially available.
[0030] The charcoal powder was homemade, with an average particle size of 200 mesh and a specific surface area of 1800 m². 2 / g, with an average pore size of 2.8 nm.
[0031] Walnut shell charcoal powder, homemade, with an average particle size of 200 mesh and a specific surface area of 2080 m². 2 / g, with an average pore size of 2.2nm.
[0032] The thermoplastic phenolic resin, selected from Jinan Shengquan Group, has a number-average molecular weight of 650.
[0033] Example 1
[0034] A method for preparing pulverized molded wood-based activated carbon includes the following steps:
[0035] S1. Charcoal powder was soaked in a 5 mol / L NaOH aqueous solution and hydrothermally reacted at 75℃ for 8 h. After the reaction was completed, the solid was collected by centrifugation and washed with pure water until the filtrate was neutral. Then, it was dried at 70℃ to constant weight to obtain hydroxylated charcoal powder. Hydroxylated charcoal powder, 3-mercaptopropyltriethoxysilane, and p-toluenesulfonic acid were added to isopropanol in a mass ratio of 100:25:3 and reacted at 70℃ for 5 h. After the reaction was completed, the solid was centrifuged, washed three times with ethanol, and dried at 70℃ to constant weight to obtain mercaptolated charcoal powder.
[0036] S2. Thiol-modified charcoal powder was dispersed in DMF, and 4-(allyloxy)benzaldehyde and 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylphenylacetone were added (the mass ratio of thiolated charcoal powder, 4-(allyloxy)benzaldehyde, and 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylphenylacetone was 100:15:0.5). The mixture was stirred at high speed to form a uniform dispersion. The dispersion was then placed under a UV lamp (365 nm, 800 W, 8 cm distance) and irradiated for 8 min under nitrogen protection to allow the thiol groups to undergo a click reaction with the alkenyl groups. After irradiation, the mixture was centrifuged, the solid was collected, washed three times with DMF, and dried under vacuum at 60 °C to constant weight to obtain modified charcoal powder.
[0037] S3. Modified wood charcoal powder, thermoplastic phenolic resin, hexamethylenetetramine, and ethanol-water mixed solvent (ethanol volume percentage 70%) are mixed and kneaded at 45℃ for 1.5 h to form a mixed wet material. The mixed wet material is extruded under high pressure (15 MPa) to obtain a shaped wet material (columnar, 2 cm long, 4 mm in diameter). The shaped wet material is first dried at 55℃ for 6 h, then dried at 80℃ for 6 h, and then heated to 160℃ and held for 1.5 h to allow the phenolic resin to complete curing and crosslinking, thus obtaining the shaped wood charcoal precursor.
[0038] S4. Place the shaped charcoal precursor in a carbonization and activation integrated furnace, and under a nitrogen atmosphere, heat it to 500℃ at a heating rate of 10℃ / min, and hold it for carbonization for 1.5 h; continue to heat it to 950℃ at a heating rate of 10℃ / min, and immediately introduce water vapor into the furnace (flow rate of 5mL / min), and hold it for activation for 3 h; after activation, allow it to cool naturally to room temperature to obtain shaped wood-based activated charcoal resistant to pulverization.
[0039] Example 2
[0040] The rest is the same as in Example 1, except that in step S2, the mass ratio of mercapto-modified charcoal powder, 4-(allyloxy)benzaldehyde, and 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylphenylacetone is 100:10:0.5.
[0041] Example 3
[0042] The rest is the same as in Example 1, except that in step S2, the mass ratio of mercapto-modified charcoal powder, 4-(allyloxy)benzaldehyde, and 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylphenylacetone is 100: 20:0.5.
[0043] Example 4
[0044] The rest is the same as in Example 1, except that in step S3, the modified wood charcoal powder is mixed with thermoplastic phenolic resin, hexamethylenetetramine, and ethanol-water in a ratio of 100:20:5:20.
[0045] Example 5
[0046] The rest is the same as in Example 1, except that in step S3, the modified wood charcoal powder is mixed with thermoplastic phenolic resin, hexamethylenetetramine, and ethanol-water in a ratio of 100:30:8:20.
[0047] Example 6
[0048] The rest is the same as in Example 1, except that in step S2, 3-(allyloxy)benzaldehyde is used in place of 4-(allyloxy)benzaldehyde by mass.
[0049] Example 7
[0050] The rest is the same as in Example 1, except that in step S2, 4-allylbenzaldehyde is used in place of 4-(allyloxy)benzaldehyde by mass.
[0051] Example 8
[0052] The rest is the same as in Example 1, except that: in step S1, 3-mercaptopropyltrimethoxysilane is used instead of 3-mercaptopropyltriethoxysilane, and the hydroxylated wood charcoal powder, 3-mercaptopropyltrimethoxysilane, and p-toluenesulfonic acid are in a mass ratio of 100:15:1; in step S3, trimethylhexamethylenediamine is used instead of hexamethylenetetramine by mass.
[0053] Example 9
[0054] The rest is the same as in Example 1, except that in step S1, walnut shell charcoal powder is used instead of wood charcoal powder.
[0055] Comparative Example 1
[0056] The rest is the same as in Example 1, except that steps S1 and S2 are omitted. Unmodified charcoal powder is directly mixed with thermoplastic phenolic resin, hexamethylenetetramine, and an ethanol-water mixed solvent in a mass ratio of 100:25:6:20, kneaded, extruded, dried, cured, and carbonized for activation. Specifically:
[0057] S1, omitted;
[0058] S2, omitted;
[0059] S3. Wood charcoal powder, thermoplastic phenolic resin, hexamethylenetetramine, and ethanol-water mixed solvent (ethanol volume percentage 70%) are mixed and kneaded at 45℃ for 1.5 h to form a mixed wet material. The mixed wet material is extruded under high pressure (15MPa) to obtain a shaped wet material (columnar, 2 cm long, 4 mm in diameter). The shaped wet material is first dried at 55℃ for 6 h, then dried at 80℃ for 6 h, and then heated to 160℃ and held for 1.5 h to allow the phenolic resin to complete curing and crosslinking, thus obtaining the shaped charcoal precursor.
[0060] S4, Same as Example 1.
[0061] Comparative Example 2
[0062] The rest is the same as in Example 1, except that in step S2, the mass ratio of mercapto-modified charcoal powder, 4-(allyloxy)benzaldehyde, and 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylphenylacetone is 100: 5:0.3.
[0063] Testing and Analysis
[0064] 1. Specific surface area test
[0065] The pore structure of the molded wood-based activated carbon prepared in the above examples and comparative examples was determined using a BSD-660M high-performance specific surface area and micropore analyzer from Best Instruments Technology (Beijing) Co., Ltd. The specific surface area of the samples was calculated by testing the N2 adsorption-desorption isotherms of the samples using the BET method.
[0066] 2. Anti-chalking performance test
[0067] The anti-pulverization performance of the molded wood-based activated carbon prepared in the above embodiments and comparative examples was tested, and the pulverization abrasion coefficient (DA) and abrasion resistance (%) were used for evaluation.
[0068] Pulverization abrasion coefficient (DA): Tested according to ASTM D5159, "Standard Test Method for Pulverization Abrasion of Granular Activated Carbon". This test simulates slow friction between particles using a vibration device, quantifying the resistance to pulverization as the amount of dust generated per unit time and per unit mass of carbon (pulverization abrasion coefficient DA). The lower the pulverization abrasion coefficient DA, the better the resistance to pulverization of the sample.
[0069] Abrasion resistance: Abrasion resistance is tested according to GB / T 12496.6-1999. This test uses a rotating drum device, subjecting the sample to rolling friction under the action of steel balls. The abrasion resistance is expressed as the percentage (%) of the mass remaining above a 1.0 mm aperture test sieve after wear. Higher abrasion resistance indicates better resistance to pulverization.
[0070] The test results are summarized in Table 1.
[0071] Table 1 Anti-chalking properties
[0072]
[0073] As can be seen from Table 1, the pulverization abrasion coefficient of the shaped activated carbon prepared in the examples is low, all ≤0.35 mg / g·min, and the wear resistance is high, all above 93%. This indicates that the shaped activated carbon in the examples has excellent anti-pulverization performance. At the same time, the specific surface area of the activated carbon did not change significantly before and after molding.
[0074] A comparison of Examples 1-3 shows that the anti-chalking performance first improves and then stabilizes with increasing alkenyl aromatic aldehyde content. Considering economic benefits, the preferred mass ratio of thiolized wood charcoal powder to alkenyl aromatic aldehyde is 100:10-15. A comparison of Examples 1 and 4-5 shows that the anti-chalking performance gradually improves with increasing thermoplastic phenolic resin and curing agent content. A ratio of modified wood charcoal powder to thermoplastic phenolic resin and curing agent of 100:(25-30):(6-8) is more preferred. Example 9 uses walnut shell charcoal powder instead of wood charcoal powder, and its anti-chalking performance is slightly better than that of Example 1. This is mainly due to the fact that walnut shell charcoal itself is denser and harder than wood charcoal.
[0075] The anti-pulverization performance of Comparative Example 1 was significantly worse, indicating that physical bonding alone is insufficient to resist pulverization abrasion. Comparative Example 2 used a smaller amount of alkenyl aromatic aldehyde, and the resulting wood-based activated carbon also exhibited worse anti-pulverization performance than the examples.
Claims
1. A method for preparing pulverized molded wood-based activated carbon, characterized in that, Includes the following steps: S1. After hydroxylation treatment, wood charcoal powder is modified with a silane coupling agent containing thiol groups to obtain thiolized wood charcoal powder. S2. Thiolized wood charcoal powder is dispersed in a polar aprotic solvent, and an alkenyl aromatic aldehyde and a photoinitiator are added to form a dispersion. The mass ratio of the thiolized wood charcoal powder to the alkenyl aromatic aldehyde is 100:10~20. Then, under the protection of an inert gas, the dispersion is irradiated with ultraviolet light to cause the thiol and alkenyl groups to undergo a click reaction. After the irradiation is completed, the mixture is purified to obtain modified wood charcoal powder. S3. The modified wood charcoal powder is mixed and kneaded with thermoplastic phenolic resin, curing agent and solvent to form a mixed wet material, which is then extruded under high pressure to obtain a molded wet material; after drying, the molded wet material is heated and cured to obtain a molded wood charcoal precursor. S4. After carbonization and activation, the shaped wood charcoal precursor is used to obtain shaped wood activated carbon resistant to pulverization.
2. The preparation method according to claim 1, characterized in that, In step S1, the wood charcoal powder is selected from at least one of bamboo charcoal powder, wood charcoal powder, coconut shell charcoal powder, and walnut shell charcoal powder, and the average particle size of the wood charcoal powder is 150-400 mesh, and the specific surface area is 1800-2200 m². 2 / g, with an average pore size of 2~10 nm. The hydroxylation treatment conditions are as follows: wood charcoal powder is soaked in an inorganic alkaline aqueous solution of 3~6 mol / L, subjected to hydrothermal reaction at 70~80℃ for 6~10 h, then centrifuged, washed with pure water until the filtrate is neutral, and dried at 60~80℃ to constant weight.
3. The preparation method according to claim 1, characterized in that, In step S1, the thiol-containing silane coupling agent is selected from at least one of 3-mercaptopropyltriethoxysilane and 3-mercaptopropyltrimethoxysilane; the modification conditions are as follows: hydroxylated wood charcoal powder, thiol-containing silane coupling agent and acid catalyst are added to alcohol at a mass ratio of 100:(15~25):(1~3), and reacted at 60~80℃ for 3~6h. After the reaction is completed, the solid is centrifuged, and the solid is washed with alcohol 2~4 times and dried at 60~80℃ to constant weight.
4. The preparation method according to claim 1, characterized in that, In step S2, the mass ratio of the thiolized wood charcoal powder to the alkenyl aromatic aldehyde is 100:10~15; the mass of the photoinitiator accounts for 0.3~0.8 wt% of the thiolized wood charcoal powder.
5. The preparation method according to claim 1, characterized in that, In step S2, the alkenyl aromatic aldehyde is an aromatic compound containing an alkenyl and an aldehyde group in its molecule, specifically selected from at least one of 3-(allyloxy)benzaldehyde, 4-(allyloxy)benzaldehyde, and 4-allylbenzaldehyde, preferably 3-(allyloxy)benzaldehyde or 4-(allyloxy)benzaldehyde.
6. The preparation method according to claim 1, characterized in that, In step S2, the polar aprotic solvent is selected from at least one of N,N-dimethylacetamide, N,N-dimethylformamide, and N-methylpyrrolidone; the photoinitiator is selected from at least one of 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylphenylacetone, 1-hydroxy-cyclohexyl-phenyl ketone, and 2-hydroxy-2-methyl-1-phenyl-1-propanone; the inert gas is selected from nitrogen and / or argon; the ultraviolet irradiation conditions are: the ultraviolet lamp is 5-10 cm above the surface of the dispersion, irradiated at 600-900 W for 5-10 min, and the ultraviolet lamp wavelength is 300-400 nm; the purification process is: centrifugation is performed sequentially, the solid part is washed 2-4 times with a polar aprotic solvent, and dried at 60-80℃ for 8-24 h.
7. The preparation method according to claim 1, characterized in that, In step S3, the ratio of the modified wood charcoal powder to the thermoplastic phenolic resin and curing agent is 100:(20~30):(5~8), preferably 100:(25~30):(6~8); the number average molecular weight of the thermoplastic phenolic resin is 500~900; the curing agent is selected from at least one of hexamethylenetetramine, trimethylhexamethylenediamine, and diethylaminopropylamine; the solvent is an alcohol solvent, or an alcohol-water mixture with an alcohol volume percentage of 70~80%, wherein the alcohol is at least one of ethanol, propanol, and isopropanol.
8. The preparation method according to claim 1, characterized in that, In step S3, the mixing and kneading temperature is 35~50℃, and the kneading and mixing time is 1~2 h; the solvent content in the mixed wet material is 10~15wt%; the high-pressure extrusion pressure is 12~18 MPa; and / or, The drying conditions are as follows: first dry at 50~60℃ for 6~12 h, then dry at 70~90℃ for 6~12 h; the curing conditions are as follows: heat to 150~180℃ and keep warm for 1~2 h.
9. The preparation method according to claim 1, characterized in that, In step S4, the carbonization conditions are as follows: under an inert atmosphere, the temperature is increased to 500-700℃ at a heating rate of 5-10℃ / min and held for 1-3 h; the activation conditions are as follows: at 850-1050℃, water vapor is introduced and activated for 2-4 h.
10. Anti-pulverization molded wood-based activated carbon prepared by the preparation method according to any one of claims 1-9.
Citation Information
Patent Citations
Shaped activated carbon as well as preparation method and application thereof
CN119461369A
